Adherence to the World Health Organization's physical activity recommendation in preschool-aged children: a systematic review and meta-analysis of accelerometer studies - Matthew Bourke; Ameena Haddara; Aidan Loh; Valerie Carson; Becky Breau; Patricia Tucker (BMC, 2023)
Abstract Background The World Health Organization (WHO) recommend that preschool-aged children should engage in 180 min of total physical activity (TPA) including 60 min of moderate-to-vigorous physical activity (MVPA) each day. No systematic reviews or meta-analyses have pooled adherence to the recommendation across multiple studies. This study aimed to estimate the prevalence of preschool-aged children achieving the WHO's physical activity recommendation for young children, and determine if the prevalence differed between boys and girls. Methods Primary literature searches were conducted on six online databases and a machine learning assisted systematic review was used to identify relevant studies. Studies written in English reporting on the prevalence of children aged 3-5 years achieving overall WHO physical activity recommendation or the individual TPA or MVPA aspects of the recommendation measured using accelerometers were eligible for inclusion. Random effects meta-analysis was used to determine the prevalence of preschools achieving the overall WHO recommendation and the individual TPA and MVPA aspect of the recommendation, and to determine difference in prevalence between boys and girls. Results Forty-eight studies reporting on 20,078 preschool-aged children met the inclusion criteria. Based on the most commonly employed accelerometer cut-points across all aspects of the recommendation, 60% (95% Confidence Interval [CI] = 37%, 79%) of preschool-aged children adhered to the overall physical activity recommendation, 78% (95% CI = 38%, 95%) adhered to the TPA aspect of the recommendation, and 90% (95% CI = 81%, 95%) adhered to the MVPA aspect of the recommendation. There was substantial variability is prevalence estimates between different accelerometer cut-points. Girls were significantly less likely to achieve the overall recommendation and the MVPA aspect of the recommendation than boys were. Conclusions Although there was substantial variability in estimated prevalence of preschool-aged children adhering the WHO physical activity recommendation between various accelerometer cut-points, the weight of available evidence suggests that the majority of young children are adhering to the overall recommendation and the individual TPA and MVPA aspects of the recommendation. Large-scale, intercontinental surveillance studies are needed to further strengthen the evidence regarding the prevalence of preschool-aged children achieving physical activity recommendation globally.